Casting aluminum alloy, aluminum alloy member, and method for manufacturing aluminum alloy member
The casting aluminum alloy with specific composition and artificial aging treatment without solution treatment addresses the need for high mechanical strength aluminum alloy members, achieving excellent mechanical properties while reducing costs and environmental impact.
Patent Information
- Application Number
- JP2022181764
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-11-14
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2042-11-14
AI Technical Summary
There is a demand for aluminum alloy members with good mechanical strength, and existing manufacturing methods often require costly solution treatments and result in higher CO2 emissions.
A casting aluminum alloy with a composition of 4.0-7.5% Si, 1.5-4.0% Cu, 1.0% or more Zn, 0.2-0.8% Mg, and the remainder Al and inevitable impurities, which is subjected to an artificial aging treatment without a solution treatment.
This approach enables the production of aluminum alloy members with tensile strength of 230 MPa or more, 0.2% yield strength of 180 MPa or more, high cycle fatigue strength of 100 MPa or more, and low cycle fatigue strength of 8,000 cycles or more, while reducing material costs and energy consumption.
Smart Images

Figure 0007666489000003 
Figure 0007666489000004 
Figure 0007666489000005
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a casting aluminum alloy, an aluminum alloy member, and a method for producing an aluminum alloy member. [Background technology]
[0002] Examples of such methods for producing an aluminum alloy member include a method for producing an aluminum alloy member in which an aluminum alloy casting is solution-treated, and a method for producing an aluminum alloy member disclosed in Patent Document 1. In the method for producing an aluminum alloy member disclosed in Patent Document 1, an aluminum alloy cast material is heated and held within a solid-liquid coexistence temperature range, and then the aluminum alloy cast material is quenched. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2019-157231 A Summary of the Invention [Problem to be solved by the invention]
[0004] The present inventors have discovered the following problems. There is a demand for aluminum alloy members having good mechanical strength. There is also a demand for casting aluminum alloys capable of producing aluminum alloy members having good mechanical strength, and for methods of producing such aluminum alloy members. In addition, in terms of the casting aluminum alloys and methods of producing aluminum alloy members, it is desirable to produce aluminum alloy members having good mechanical strength without carrying out solution treatment, from the viewpoints of reducing material costs, saving energy, reducing CO2 emissions, etc.
[0005] The present disclosure has been made in consideration of the above-mentioned problems, and aims to provide an aluminum alloy for casting, an aluminum alloy part, and a method for manufacturing an aluminum alloy part, each of which has good mechanical strength. [Means for solving the problem]
[0006] The casting aluminum alloy according to the present disclosure contains, by mass%, 4.0-7.5% Si, 1.5-4.0% Cu, 1.0% or more Zn, 0.2-0.8% Mg, and the balance being Al and unavoidable impurities.
[0007] According to this configuration, by increasing the Zn and Mg contents, an aluminum alloy part having good mechanical strength can be manufactured.
[0008] In the above-mentioned casting aluminum alloy, the Zn content may be limited to 1.0% to 5.0% by mass, and the Mg content may be limited to 0.5% to 0.8% by mass.
[0009] According to this configuration, by increasing the lower limit of the Zn or Mg content, it is possible to stabilize the mechanical strength.
[0010] In the above-mentioned aluminum alloy for casting, the Si content may be limited to 4.0% or more and less than 5.0% by mass, or the Cu content may be limited to 1.5% or more and less than 2.0% by mass.
[0011] According to this configuration, by limiting the content of Si or Cu, an increase in material costs can be suppressed.
[0012] The aluminum alloy member according to the present disclosure is made of a casting aluminum alloy containing, by mass%, 4.0-7.5% Si, 1.5-4.0% Cu, 1.0% or more Zn, 0.2%-0.8% Mg, and the balance being Al and unavoidable impurities, and has a tensile strength of 230 MPa or more, a 0.2% yield strength of 180 MPa or more, a high-cycle fatigue strength of 100 MPa or more, and a low-cycle fatigue strength of 8,000 cycles or more.
[0013] According to this configuration, by increasing the Zn and Mg contents, an aluminum alloy part having good mechanical strength can be manufactured.
[0014] In addition, in the above-mentioned aluminum alloy member, it is preferable that Mg5Si6 that can be measured using a TEM is precipitated.
[0015] According to this configuration, the mechanical strength can be improved by the precipitation of Mg5Si6.
[0016] A method for producing an aluminum alloy member according to the present disclosure includes the steps of: casting an aluminum alloy for casting containing, by mass%, 4.0 to 7.5% Si, 1.5 to 4.0% Cu, 1.0% or more Zn, 0.2 to 0.8% Mg, and the balance being Al and unavoidable impurities, to form an aluminum casting material; and a step of heating and holding the cast aluminum material at a heating temperature of 185 to 205° C. to subject the cast aluminum material to artificial aging treatment.
[0017] According to this configuration, an aluminum alloy part having good mechanical strength can be manufactured using a casting aluminum alloy having an increased content of Zn and Mg. Effect of the Invention
[0018] According to the present disclosure, an aluminum alloy part having good mechanical strength can be manufactured. [Brief description of the drawings]
[0019] [Figure 1] FIG. 1 is a flowchart of a method for manufacturing an aluminum alloy member according to the first embodiment. [Diagram 2] FIG. 2 is a diagram showing an example of a heat treatment pattern showing a change in temperature with respect to time. [Diagram 3] FIG. 3 is a graph showing an example of the tensile strength test results of T5 material. [Figure 4]FIG. 4 is a graph showing another example of the tensile strength test results of the T5 material. [Diagram 5] FIG. 5 is a graph showing an example of the tensile strength test results of T6 material. [Figure 6] FIG. 6 is a graph showing an example of the hardness test results of the F material. [Figure 7] FIG. 7 is a graph showing an example of the results of a high-temperature low-cycle fatigue test. [Figure 8] FIG. 8 is a graph showing an example of the results of comparing fatigue lives. [Figure 9] FIG. 9 is a graph showing an example of the results of a high-temperature low-cycle fatigue test on the T6 material. [Figure 10] FIG. 10 is a graph showing an example of the high-temperature low-cycle fatigue test results. [Figure 11] FIG. 11 is a graph showing an example of the high cycle fatigue test results of the T5 material. [Figure 12] FIG. 12 is a graph showing an example of the high cycle fatigue test results of the T6 material. [Figure 13] FIG. 13 is a graph showing an example of the results of comparing high cycle fatigue strength. [Figure 14] FIG. 14 is a graph showing the relationship between the Zn content and the required heat treatment time. [Figure 15] FIG. 15 is a diagram showing the results of EPMA analysis of the aluminum alloy member according to Example 4. [Figure 16] Fig. 16(a) is a diagram showing the results of TEM analysis of the aluminum alloy member according to Example 4. Fig. 16(b) is an enlarged view showing the results of TEM analysis of the aluminum alloy member according to Example 4. [Figure 17] FIG. 17 is a diagram showing the results of EPMA analysis of the aluminum alloy member according to Comparative Example 1. [Figure 18] Fig. 18(a) is a diagram showing the results of TEM analysis of the aluminum alloy structural member according to Comparative Example 1. Fig. 18(b) is an enlarged view showing the results of TEM analysis of the aluminum alloy structural member according to Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] Hereinafter, specific embodiments to which the present invention is applied will be described in detail with reference to the drawings. However, the present invention is not limited to the following embodiments. In addition, the following description and drawings are appropriately simplified for clarity of explanation.
[0021] <Embodiment 1> The casting aluminum alloy according to the first embodiment will be described.
[0022] The aluminum alloy for casting according to the first embodiment contains, by mass%, 4.0-7.5% Si, 1.5-4.0% Cu, 1.0% or more Zn, 0.2-0.8% Mg, and the balance being Al and unavoidable impurities, such as Fe, Mn, etc.
[0023] In the chemical composition of the casting aluminum alloy according to the first embodiment, when the content of Si is in a suitable range, a predetermined castability can be ensured. Therefore, casting defects such as cracks and shrinkage cavities are unlikely to occur in the aluminum alloy casting material. On the other hand, when the content of Si is too high, a large amount of brittle Si particles are crystallized in the aluminum alloy casting material, and mechanical properties such as breaking elongation and strength tend to decrease. Therefore, the content of Si is preferably in the range of 4.0% to 7.5% by mass. In addition, the content of Si is preferably limited to 4.0% to less than 5.0% by mass. Since Si tends to be expensive compared to Zn and Mg, when the content of Si is limited in this way, the material cost of the casting aluminum alloy can be suppressed while ensuring good mechanical strength.
[0024] In addition, when the Cu content is in a suitable range, Al-Cu compounds are precipitated in the metal structure of the aluminum alloy member by artificial aging, and Al-Mg-Si-Cu compounds are precipitated in the metal structure of the aluminum alloy member. The Al-Cu compound is, for example, CuA12. These can improve the mechanical strength of the aluminum alloy member, such as tensile strength and 0.2% proof stress. On the other hand, if the Cu content is too high, the ductility and toughness of the aluminum alloy member may decrease. Therefore, the Cu content is preferably in the range of 1.5 to 4.0% by mass. In addition, the Cu content is preferably limited to 1.5% or more and less than 2.0% by mass. Since Cu tends to be expensive compared to Zn and Mg, if the Cu content is limited in this way, the material cost of the aluminum alloy for casting can be suppressed while maintaining good mechanical strength. In addition, since there is no established technology for removing Cu from the aluminum alloy, it is desirable from the viewpoint of recycling to limit the Cu content in this way.
[0025] In addition, when the Zn content is within a suitable range, the Zn atoms are dissolved in the aluminum crystals in the aluminum alloy member, and the mechanical strength of the aluminum alloy member can be improved. In addition, since the Zn atoms dissolved in the aluminum crystals are precipitation nuclei of compounds during artificial aging, the aluminum alloy member can be given the necessary mechanical strength with a short artificial aging treatment time. That is, the artificial aging treatment time of the cast aluminum alloy material can be shortened. Therefore, the Zn content is preferably 1.0% or more by mass. In addition, the Zn content is preferably limited to 1.0% or more and 8.0% or less by mass. This is because if the Zn content exceeds 8.0%, the effect of shortening the artificial aging treatment time of the cast aluminum alloy material is almost lost. In addition, if the Zn content is 8.0% or less, the material cost can be suppressed.
[0026] In addition, the Zn content is preferably limited to 1.0% to 5.0% by mass, because by reducing the Zn content, material costs can be reduced while maintaining good mechanical properties.
[0027] Furthermore, when the Mg content is within a suitable range, Al-Mg-Si-Cu compounds and Mg-Si compounds are precipitated in the metal structure of the aluminum alloy member by artificial aging treatment. An example of the Mg-Si compound is Mg5Si6. The precipitation of the Mg-Si compounds can improve the mechanical strength of the aluminum alloy member, such as tensile strength and hardness. On the other hand, if the Mg content is too high, the elongation decreases. Therefore, it is preferable that the Mg content is 0.2% or more and 0.8% or less.
[0028] The Mg content may be limited to 0.5% to 0.8% by mass. When the Mg content is 0.5% or more by mass, Mg-Si compounds are stably precipitated in the metal structure of the aluminum alloy member by artificial aging treatment. This can further improve the mechanical strength of the aluminum alloy member.
[0029] The remaining inevitable impurities in the casting aluminum alloy according to the present embodiment 1 are, for example, Fe and Mn. When the casting aluminum alloy according to the present embodiment 1 contains Fe or Mn as an inevitable impurity, the Fe content may be limited to 1.0% or less by mass, and the Mn content may be limited to 1.0% or less by mass.
[0030] <Method of manufacturing aluminum alloy member> Next, an example of a method for producing an aluminum alloy structural member using the casting aluminum alloy according to the first embodiment will be described with reference to FIG.
[0031] The aluminum alloy for casting is cast to form an aluminum alloy casting material (step ST1). Specifically, the aluminum alloy for casting is heated and melted to obtain a molten metal. The molten metal is poured into a mold and cooled and solidified in the mold to form an aluminum alloy casting material. The aluminum alloy casting material is released from the mold. The aluminum alloy casting material has a wide variety of shapes, such as a cylinder head, a turbo part, etc.
[0032] Subsequently, the aluminum alloy cast material is subjected to an artificial aging treatment (step ST2). Specifically, after the demolding of the aluminum alloy cast material is completed, air is blown onto the aluminum alloy cast material to cool it. At the time when the air blowing to the aluminum alloy cast material is started, the temperature of the aluminum alloy cast material may be, for example, 300°C or higher. The cooling rate in this cooling may be, for example, 30°C / min or higher. The air blowing to the aluminum alloy cast material may be continued until the temperature of the aluminum alloy cast material reaches, for example, 110°C. Thereafter, the aluminum alloy cast material is heated and held at the aging treatment temperature for a predetermined time, and the aluminum alloy cast material is subjected to an artificial aging treatment to manufacture an aluminum alloy member. The aging treatment temperature is, for example, 185 to 205°C. The predetermined time may be, for example, 180 min. Furthermore, the aluminum alloy member may be allowed to cool.
[0033] From the above, an aluminum alloy member can be manufactured. As described below, this aluminum alloy member has good mechanical strength. This aluminum alloy member is a T5 material because it has been subjected to only artificial aging treatment without being subjected to solution treatment. Therefore, an aluminum alloy member having good mechanical strength can be manufactured without being subjected to solution treatment.
[0034] Note that an aluminum alloy structural member may be manufactured by performing only step ST1 above using the casting aluminum alloy according to the first embodiment, without performing step ST2 above. That is, the aluminum alloy cast material may be used as the aluminum alloy structural member. In this case, the aluminum alloy structural member is a casting that has not been subjected to heat treatment, that is, an F material.
[0035] Alternatively, an aluminum alloy structural member may be manufactured by carrying out the above-mentioned step ST1 using the casting aluminum alloy according to the first embodiment, and then carrying out a solution treatment on the cast aluminum alloy material, followed by carrying out the above-mentioned step ST2. In this case, the cast aluminum alloy material is the aluminum alloy structural member. In this case, the aluminum alloy structural member is a T6 material. EXAMPLES
[0036] Next, various tests were carried out to measure the mechanical strength of the examples of the casting aluminum alloy according to embodiment 1. The results will be described.
[0037] <Tensile test> First, the results of the tensile test will be described.
[0038] In Examples 1 to 5 and 8, the aluminum alloy members were produced from casting aluminum alloys having the respective composition shown in Table 1, using the example of the method for producing the aluminum alloy member shown in Fig. 1. The heat treatment conditions in Examples 1 to 5 and 8 are shown in Table 2. [Table 1] [Table 2]
[0039] In Example 6, a casting aluminum alloy having the same composition as in Example 4 was cast to form a turbo part as an aluminum alloy member, and the turbo part was subjected to a solution treatment and an artificial aging treatment, i.e., a T6 treatment. The turbo part was a T6 material. The treatment conditions for the solution treatment were a solution temperature of 490°C and a treatment time of 2.0 hours. The treatment conditions for the artificial aging treatment were an aging temperature of 210°C and a treatment time of 2.0 hours.
[0040] In Example 7, a turbo part was formed as an aluminum alloy member by casting an aluminum alloy having the same composition as in Example 4. The turbo part was a casting that was not heat-treated, that is, an F material.
[0041] In Comparative Example 1, an aluminum alloy member was produced from a casting aluminum alloy having the composition of Comparative Example 1 shown in Table 1, using the example of the method for producing an aluminum alloy member shown in Fig. 1. The casting aluminum alloy of Comparative Example 1 is an aluminum alloy having a composition within the range specified by JIS AC2B. The heat treatment conditions of Comparative Example 1 are shown in Table 2.
[0042] In Comparative Example 2, a casting aluminum alloy having the same composition as Comparative Example 1 was cast to form a turbo part. Furthermore, the turbo part was subjected to a solution treatment and an artificial aging treatment, i.e., a T6 treatment. The turbo part was a T6 material. The treatment conditions for the solution treatment were a solution temperature of 490°C and a treatment time of 2.0 hours. The treatment conditions for the artificial aging treatment were an aging temperature of 210°C and a treatment time of 2.0 hours.
[0043] In Comparative Example 3, a turbo part was formed by casting an aluminum alloy for casting having the same composition as that of Comparative Example 1. The turbo part was a casting that had not been heat-treated, that is, an F material.
[0044] In Examples 1 to 8 and Comparative Examples 1 to 3, the static strength and fatigue properties of the aluminum alloy members produced as described above were measured. The static strengths were tensile strength, 0.2% yield strength, and butt elongation. The fatigue properties were high cycle fatigue strength and high temperature low cycle fatigue strength. The high cycle fatigue strength was measured at 10 7 The load that does not break is 10 times. 7It is the maximum strength at which a load of 0.22 (MPa·Strain) can be repeatedly applied to a test piece without causing breakage in a thermal fatigue test. The low cycle fatigue life is the number of cycles at which a load of 0.22 (MPa·Strain) is repeatedly applied to a test piece in a thermal fatigue test until the test piece breaks. The tensile strength, butt elongation, 0.2% proof stress, high cycle fatigue strength, and low cycle fatigue strength of Examples 1 to 5 and Comparative Example 1 are shown in Table 2. The results of measuring each static strength and fatigue property are shown in Figs. 3 to 13.
[0045] In this mechanical strength measurement test, the mechanical strength is judged to be good if the tensile strength is 230 MPa or more, the 0.2% yield strength is 180 MPa or more, the butt elongation is 1.0% or more, the high cycle fatigue strength is 100 MPa or more, and the low cycle fatigue strength is 8,000 cycles or more.
[0046] As shown in Table 2, in Examples 1 to 5 and 8, the tensile strength, butt elongation, 0.2% proof stress, high cycle fatigue strength, and low cycle fatigue strength are equal to or greater than the above values, and therefore the mechanical strength is judged to be good. On the other hand, the butt elongation of Comparative Example 1 is equal to or greater than the above values, but the tensile strength, 0.2% proof stress, high cycle fatigue strength, and low cycle fatigue strength of Comparative Example 1 are lower than the above values, except for the butt elongation. Therefore, the mechanical strength of Comparative Example 1 is judged to be poor. Note that, as shown in Table 2, the tensile strength, 0.2% proof stress, butt elongation, high cycle fatigue strength, and low cycle fatigue strength of Example 8 are almost the same as those of Example 5. As shown in Tables 1 and 2, Example 5 has a lower Cu and Si content than Example 8, but the static strength and fatigue properties are almost the same.
[0047] <Tensile strength test results> The results of the tensile strength test will be described with reference to Figures 3 to 5. Figures 3 and 4 show an example of the results of the tensile strength test for T5 material, and Figure 5 shows an example of the results of the tensile strength test for T6 material.
[0048] 3, the tensile strength and 0.2% yield strength of Examples 1, 2, and 5 were all higher than those of Comparative Example 1. One reason for this is that Examples 1, 2, and 5 have higher Zn and Mg contents than Comparative Example 1.
[0049] 4, the tensile strength and 0.2% yield strength of Example 4 were both higher than those of Comparative Example 1. One of the reasons for this is that Example 4 had higher Zn and Mg contents than Comparative Example 1. The butt elongation of Example 4 was 1.4%, which was almost the same value as that of Comparative Example 1 and was good.
[0050] 5, the tensile strength and 0.2% proof stress of Example 6 were almost the same as those of Comparative Example 2, and were good. The butt elongation of Example 6 was higher than that of Comparative Example 2. One of the reasons for this is that Example 6 contains higher Zn and Mg contents than Comparative Example 2.
[0051] <Hardness test results> The results of the hardness test of the F material will be described with reference to Fig. 6. Fig. 6 shows an example of the results of the hardness test of the F material.
[0052] As shown in Fig. 6, the Brinell hardness of Example 7 is higher than that of Comparative Example 3, and the Brinell hardness of Example 7 is about 130% of that of Comparative Example 3. That is, the Brinell hardness of Example 7 is equal to a value that is about 30% higher than that of Comparative Example 3. Since the Brinell hardness tends to be proportional to the mechanical strength, it can be inferred that Example 7 has a higher mechanical strength than Comparative Example 3. One reason for this is that Example 7 has a higher Zn and Mg content than Comparative Example 3.
[0053] <High temperature low cycle fatigue test results> The high-temperature low-cycle fatigue test results will be described with reference to Fig. 7 to Fig. 9. Fig. 7 is a graph showing an example of the high-temperature low-cycle fatigue test results. Fig. 8 is a graph showing an example of the results of comparing fatigue lives. Fig. 9 is a graph showing an example of the high-temperature low-cycle fatigue test results for T6 material.
[0054] 7 shows, as an example of the high-temperature low-cycle fatigue test results, the SN curves of Examples 4 and 5 and the SN curve of Comparative Example 1. The SN curves of Examples 4 and 5 are plotted against the number of repetitions N f The number of repetitions N in Example 4 is calculated based on the hysteresis energy HE. f Hysteresis energy HE for the number of repetitions N in Example 5 f The hysteresis energy HE versus strain shows approximately the same tendency, and the SN curve of Example 4 is approximately the same as the SN curve of Example 5. Although the Cu and Si contents are different between Example 4 and Example 5, the high-temperature low-cycle fatigue test results are approximately the same. As shown in FIG. 7, the SN curves of Example 4 and Example 5 show a tendency that the hysteresis energy HE versus strain at 0.22 MPa·Strain or less is approximately the same as the SN curve of Comparative Example 1. f In addition, the SN curves of Examples 4 and 5 have a larger number of repetitions N at hysteresis energy HE of 0.22 MPa·Strain or less than that of Comparative Example 2. f It is almost the same as:
[0055] As shown in FIG. 8, in Example 4 and Example 5, the number of cycles N at hysteresis energy HE 0.22 MPa·Strain is smaller than that in Comparative Example 1. f , that is, the fatigue life is long. Here, the fatigue life of Example 4 and Example 5 is improved by about 30% compared to the fatigue life of Comparative Example 1. One of the reasons for this is that Example 4 and Example 5 have higher Zn and Mg contents than Comparative Example 1.
[0056] In addition, in comparison with Comparative Example 2, Examples 4 and 5 have a hysteresis energy HE of 0.22 MPa·Strain and a number of repetitions N f , and the fatigue life is not much different. Example 4 and Example 5 are T5 materials, while Comparative Example 2 is T6 material. Therefore, Example 4 and Example 5 have a high fatigue life similar to that of the T6 material without being subjected to solution treatment.
[0057] As shown in FIG. 9, Example 6 has a higher repeat number N f In other words, the fatigue life is almost the same. Example 6 has the same component composition of the casting aluminum alloy as Example 4, but is subjected to a solution treatment, unlike Example 4. Even though Example 6 is subjected to a solution treatment, the fatigue life of Example 6 is not much different from that of Comparative Example 2, and is good.
[0058] As shown in FIG. 10, the reference number of repetitions N f The reference line of the SN curve passing through 1 is determined. The number of repetitions N of the SN curve of Comparative Example 1 f is smaller than the reference line. On the other hand, the number of repetitions N f is larger than the reference line at the reference hysteresis energy HE1 or less. In Example 4, the number of repetitions N f is large.
[0059] <High cycle fatigue test results> Next, the rotating bending fatigue test results will be described with reference to Fig. 11 to Fig. 13. Fig. 11 is a graph showing an example of the high cycle fatigue test results of T5 material. Fig. 12 is a graph showing an example of the high cycle fatigue test results of T6 material. Fig. 13 is a graph showing an example of the results of comparing high cycle fatigue strength.
[0060] 11, the high cycle fatigue strength of Comparative Example 2 was about 80 MPa. On the other hand, the high cycle fatigue strength of Example 4 was about 110 MPa, which was higher than the high cycle fatigue strength of Comparative Example 2.
[0061] As shown in FIG. 12, the high-cycle fatigue strength of Example 6 was about 80 to 110 MPa, which was higher than that of Comparative Example 2. As shown in FIG. 13, the high-cycle fatigue strengths of Example 4 and Example 6 were about 110 MPa, which was about 130% of the high-cycle fatigue strength of Comparative Example 2, and was improved by about 30% from the high-cycle fatigue strength of Comparative Example 2. One of the reasons for this is that Examples 4 and 6 had higher Zn and Mg contents compared to Comparative Example 2. Example 4 is an F material, while Example 6 is a T6 material. The high-cycle fatigue strengths of Example 4 and Example 6 were both good values regardless of the presence or absence of solution treatment.
[0062] <Required heat treatment time with respect to Zn content> Next, with reference to FIG. 14, the required heat treatment time until a predetermined hardness is reached will be described for a plurality of aluminum casting alloys having different Zn contents.
[0063] For elements other than Zn, an aluminum casting alloy having a component composition within the range of the target composition shown in Table 1 is prepared. The Zn contents of the prepared aluminum casting alloys are about 0.2%, about 1.0%, about 1.5%, about 3.0%, about 5.0%, about 6.0%, and about 8.0%.
[0064] Using an example of the manufacturing method of the aluminum alloy member shown in FIG. 1, an aluminum alloy member is manufactured from the prepared aluminum casting alloy. As the heat treatment time in Step ST2 in the example of the manufacturing method of the aluminum alloy member shown in FIG. 1, in other words, as the artificial aging treatment time elapses, the hardness of the manufactured aluminum alloy member is periodically measured. This measurement is repeated until the hardness of the manufactured aluminum alloy member reaches a predetermined value. The required heat treatment time required for the hardness of the manufactured aluminum alloy member to reach a predetermined value is shown in FIG. 14.
[0065] As shown in Fig. 14, as the Zn content of the casting aluminum alloy increases, the required heat treatment time decreases. For example, when the Zn content of the casting aluminum alloy is about 0.2%, the required heat treatment time exceeded 5 hours, but when the Zn content of the casting aluminum alloy is about 1.0%, the required heat treatment time was 4 hours. When the Zn content of the casting aluminum alloy is about 5.0%, the required heat treatment time exceeded 3 hours, and when the Zn content of the casting aluminum alloy is about 8.0%, the required heat treatment time was less than 3 hours. When the Zn content of the casting aluminum alloy exceeds a predetermined value, about 5.0% or about 8.0%, the effect of suppressing the required heat treatment time is also reduced.
[0066] <Metal structure observation results> Next, the results of metallographic observation will be described with reference to Fig. 15 to Fig. 18. Fig. 15 and Fig. 16 show the results of EPMA and TEM analysis, respectively, of the aluminum alloy member according to Example 4. Fig. 17 and Fig. 18 show the results of EPMA and TEM analysis, respectively, of the aluminum alloy member according to Comparative Example 1.
[0067] 17, no Zn atoms were detected at all over the cross section of the aluminum alloy structural member according to Comparative Example 1. This may be due to the fact that the aluminum alloy structural member according to Comparative Example 1 has a limited Zn content.
[0068] On the other hand, as shown in FIG. 15, Zn atoms are distributed more uniformly in the entire cross section of the aluminum alloy part according to Example 4 compared to other elements. Specifically, most of the Zn atoms are distributed in the Al crystal grains. From these, it can be determined that most of the Zn atoms are dissolved in the Al crystal grains. As described above, Example 4 is superior in static strength and fatigue properties compared to Comparative Example 1. One of the reasons for this is solid solution strengthening by Zn atoms.
[0069] 18, it was confirmed that Al-Cu based compounds, Al-Mg-Si-Cu based compounds, and Al-Si based compounds were precipitated in the cross section of the aluminum alloy member according to Comparative Example 1. The Al-Cu based compound is, for example, Al2Cu.
[0070] On the other hand, as shown in FIG. 16, it was confirmed that Al-Cu compounds, Al-Mg-Si-Cu compounds, Al-Si compounds, and Mg-Si compounds were precipitated in the cross section of the aluminum alloy member according to Example 4. The Al-Cu compounds are, for example, Al2Cu. The Mg-Si compounds are, for example, Mg5Si6. It was confirmed that Mg-Si compounds were precipitated in the cross section of the aluminum alloy member according to Example 4, unlike that of Comparative Example 1. As described above, Example 4 is superior in static strength and fatigue properties compared to Comparative Example 1. One of the reasons for this is the precipitation strengthening of Mg-Si compounds, Mg5Si6.
[0071] In addition, it was confirmed that when the Mg content of the casting aluminum alloys according to the other examples exceeds 0.5%, Mg-Si compounds were stably precipitated on the cross section of the aluminum alloy members according to the examples. Therefore, when the Mg content of the casting aluminum alloys according to the other examples exceeds 0.5%, it is possible to improve the static strength and fatigue properties of the aluminum alloy members.
[0072] The present invention is not limited to the above-described embodiment, and can be modified as appropriate without departing from the spirit and scope of the present invention. In addition, the present invention can be implemented by appropriately combining the above-described embodiment and examples thereof. [Explanation of symbols]
[0073] ST1, ST2 steps
Claims
1. A casting aluminum alloy containing, by mass%, 4.0-7.5% Si, 1.5-4.0% Cu, 1.0-5.0% Zn, 0.2-0.8% Mg, with the balance being Al and unavoidable impurities, wherein when the unavoidable impurities include Fe or Mn, the Fe content is limited to 1.0% by mass or less, and the Mn content is limited to 1.0% by mass or less.
2. 2. The aluminum alloy for casting according to claim 1, wherein the Mg content is limited to 0.5% to 0.8% by mass.
3. 3. The aluminum alloy for casting according to claim 1 or 2, wherein the Si content is limited to 4.0% or more and less than 5.0% by mass, or the Cu content is limited to 1.5% or more and less than 2.0% by mass.
4. a casting aluminum alloy containing, by mass%, 4.0 to 7.5% Si, 1.5 to 4.0% Cu, 1.0 to 5.0% Zn, and 0.2 to 0.8% Mg, with the balance being Al and unavoidable impurities, in which when the unavoidable impurities include Fe or Mn, the content of Fe is limited to 1.0% or less, by mass%, and the content of Mn is limited to 1.0% or less, by mass%, Tensile strength is 230 MPa or more, 0.2% yield strength is 180 MPa or more, high cycle fatigue strength is 100 MPa or more, and low cycle fatigue strength is 8000 cycles or more. Aluminum alloy components.
5. Mg that can be measured using TEM 5 S 6 was precipitated, The aluminum alloy member according to claim 4.
6. a step of forming an aluminum casting material by casting an aluminum alloy containing, by mass%, 4.0 to 7.5% Si, 1.5 to 4.0% Cu, 1.0 to 5.0% Zn, and 0.2 to 0.8% Mg, with the balance being Al and unavoidable impurities, wherein when the unavoidable impurities include Fe or Mn, the Fe content is limited to 1.0% or less, and the Mn content is limited to 1.0% or less, by mass; and heating and holding the aluminum casting material at a heating temperature of 185 to 205°C to subject the aluminum casting material to artificial aging treatment. A method for manufacturing an aluminum alloy member.
Citation Information
Patent Citations
Aluminum alloy material, aluminum alloy forming part and preparation method thereof, and terminal equipment
CN111118356A
JP1972013724B1
Denshitokeino hyojisochi
JP1976042567A
al-si-mg-zn-cu alloys for aerospace and automotive castings
JP2008514807A
Manufacturing method of aluminum alloy member
JP2019157231A